DYNAMICS OF PSYCHO-PHYSIOLOGICAL PREPARATION OF 12-16-YEAR-OLD WRESTLERS - Qobulov Q. A. (Web of Journals Publishing, 2024)
This article examines physical fitness indicators and psychophysiological processes of young wrestlers during training. In the general preparation stage of the period of psychophysiological training of young wrestlers, the main attention is paid to comprehensive general physical training and psychophysiological conditions of 12-16-year-old wrestlers.
Keywords: 12-16-year-old wrestlers, psychophysiology, dynamics, training, period, wrestling, physical education, sport.